An investigation on the sperm number and reproductive parameters of males in wild caught freshwater crayfish (Astacus leptodactylus, Eschscholtz) - Harlioglu, Muzaffer Mustafa; Kutluyer, Fitiz; Gur, Seyfettin (Brill Academic Publishers, 2012)
In the present study, the sperm number of wild caught Astacus leptodactylus was counted in the beginning of reproduction season. In addition, the reproductive system, testes, and vasa deferentia were weighed, and gonado-somatic index and testicular index were calculated. Twenty-five adult males of A. leptodactylus were used for the study. Significant linear regressions were found between body length (and weight) and sperm count, reproductive system weight, testes weight and vasa deferentia weight (P < 0.05). The mean sperm number of vas deferens for the size range of 41-56 mm carapace length crayfish was 5.72 +/- 4.54 x 10(9) sperm/distal vas deferens (DVD) section. Sperm number ranged from 4 x 10(8) to 8.5 x 10(9) sperm/DVD section. The results revealed that an increase in body weight causes an increase in sperm number. For example, mean sperm number was 3.87 +/- 2.87 x 10(9) for the weight range of 15-24 g crayfish, 5.01 +/- 2.62 x 10(9) for the weight range of 25-35 g crayfish and 7.37 +/- 2.87 x 10(9) for the weight range of 36-42 g crayfish. In conclusion, this study provides some data on the male reproduction characters and needs to be improved with details about the reproductive performance of males (i.e., sperm number and quality) in order to reach a maximum reproductive efficiency in captivity.
Keywords: A. leptodactylus; crayfish; sperm number; sperm production